Induction of Biomolecules in Mature Leaves of Terminalia arjuna Due to Feeding of Antheraea mylitta Drury - G. Abraham; G. Thomas; C.R. Babu (The Scientific World Journal)
Terminalia arjuna is an important food plant of the tasar silkworm, Antheraea mylitta Drury. In this study, we investigated the induction of biomolecules in mature leaves of these plants subjected to insect feeding. Increase in total tannin content, lipid peroxidation, and trypsin inhibitor activity have been observed in mature leaves damaged by the insects. The growth rate of Vth instar larvae of A. mylitta fed on previously damaged foliage reduced by 87.1%. Induction of biomolecules for defense mechanisms in relation to herbivore damage has been discussed.